Strategi Mahasiswa KKN dalam Meningkatkan Kesejahteraan UMKM Lokal Desa Sesela Gunungsari - Ridho, Wahyu (Lembaga Publikasi Ilmiah Nusantara, 2025)
Community Service Program (KKN) is a form of community service conducted by university students to contribute directly to village development. This study aims to analyze the strategies implemented by KKN students to improve the welfare of local Micro, Small, and Medium Enterprises (MSMEs) in Sesela Gunungsari Village. Using a participatory approach, KKN students identified the potentials and challenges faced by local MSMEs and designed empowerment programs that included managerial training, digital marketing, and product quality enhancement. The results showed that the strategies implemented by KKN students were effective in improving MSME management capacity, expanding market access, and motivating MSME actors to develop their businesses more professionally. Moreover, the sustainability of the KKN program has proven to have a positive impact on increasing the income and quality of life of the Sesela Gunungsari Village community. This study is expected to serve as a reference for developing more targeted and sustainable KKN programs to support MSME development in other villages.